2002
DOI: 10.4319/lo.2002.47.4.1210
|View full text |Cite
|
Sign up to set email alerts
|

Rapid deep‐water renewal in Lake Issyk‐Kul (Kyrgyzstan) indicated by transient tracers

Abstract: Abstract-Simultaneous profiles of the transient tracers sulfur hexafluoride (SF 6 ), 3 H-3 He, and the chlorofluorocarbons CFC-11 and CFC-12 were measured in Lake Issyk-Kul, a large, deep lake in Kyrgyzstan. Apparent water ages derived from these measurements suggest rapid mixing, with a deepwater renewal rate Ͼ10% yr Ϫ1 at 650 m depth. SF 6 and 3 H-3 He ages agree reasonably well, whereas CFC ages are significantly greater. The discrepancy is explained by the nonlinear relationship between tracer age and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…Data on the transient tracers 3 H, 3 He, and SF 6 measured at Sta. 3 in 2001 (Hofer et al 2002) suggest a decrease in apparent water age at ϳ500 m depth. This observation is consistent with the interpretation that the intrusions are recent features containing water from upper regions of the water column.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data on the transient tracers 3 H, 3 He, and SF 6 measured at Sta. 3 in 2001 (Hofer et al 2002) suggest a decrease in apparent water age at ϳ500 m depth. This observation is consistent with the interpretation that the intrusions are recent features containing water from upper regions of the water column.…”
Section: Resultsmentioning
confidence: 99%
“…tracer data indicated that the water at 600 m depth has a residence time Ͻ10 yr, which suggests rapid deep-water renewal (Hofer et al 2002;Vollmer et al 2002a). New SF 6 data measured in samples collected at the deepest station (Sta.…”
Section: Speculations On Deep-water Renewal By Advective Processes Anmentioning
confidence: 99%
See 3 more Smart Citations